Building police legitimacy in a high demand environment: the case of Yukon, Canada. Issue 3 (21st August 2017) - Taylor Griffiths, Curt; Clark, Peter
Abstract : Purpose: Police legitimacy has emerged as a core concept in the study of twenty-first century policing. The purpose of this paper is to contribute new knowledge by examining the dynamics surrounding policing legitimacy in a high demand environment in Northern Canada. Design/methodology/approach: A case study approach was used to explore the historical and contemporary factors that contributed to the challenges surrounding the police-First Nations relations, how these challenges affected public confidence in, and trust of, the police, and how the communities, police, and government took action to address these issues. Findings: The findings reveal that it is possible for the police, First Nations, and government in high demand environments to implement reforms and to create the foundation for police-community collaboration. The development of relationships based on trust and a continuing dialogue is important components in building police legitimacy. Research limitations/implications: The study was conducted in one northern jurisdiction. The findings may apply to other jurisdictions where the police are involved in policing indigenous peoples. Practical implications: The case study provides insight into the processes required to fundamentally alter the police-First Nations relations, to improve police service delivery in high demand environments, and to ensure that reforms are sustained. Originality/value: Police legitimacy has been examined primarily in urban environments where police services have considerable capacities and there re-extensive networks of support from various agencies and organizations. The dynamics of policing in northern communities are appreciably different and present challenges as well as opportunities for improving police legitimacy.